Promoting Assisted-Online Platform in Evaluating Reading Exercise in English for Academic Purpose Program - Khotimah Mahmudah; Nur Arifah Drajati; Ngadiso Ngadiso (IJIE (Indonesian Journal of Informatics Education), 2018)
Along with the development of the digital era, how to pass learning evaluation can be done by using one of platforms in technology. This is no exception in the case of evaluation for academic reading at the university level. This study used Google Form as a platform for conducting an evaluation process of reading exercise. The purposes were to create a chance for university students that join in English for academic purpose program in order to evaluate a specific material outside of class, to determine the levels of difficulty from reading exercises assisted-online platform, and to determine the discrimination indexes of reading exercises assisted-online platform. This paper was qualitative-content analysis research involved fifteen university students who came from different programs. The data collection was gathered from observation and document analysis. The finding reveals that the evaluation of reading exercise can be done effectively using online platform outside of class. This result is a novelty in doing evaluation for English Teacher. In conducting a test, by using an online platform, it also indicates that the test is valid and reliable. The implication is that the online platform has several benefits in helping teachers carrying out an evaluation or developing a test of a lesson and implementing the test outside of the class as effective as in the class.